THE USE OF EDUCAPLAY IN PRIMARY SCHOOL LEARNING - Nunung Nurhayati; Karlimah Karlimah; Ghullam Hamdu (Jurnal Cakrawala Pendas, 2025)
Technological developments in education have encouraged the use of digital media in learning, including in elementary schools. One of the innovations used is Educaplay, a gamification-based platform designed to increase student engagement in the learning process. However, the effectiveness of Educaplay in improving students' conceptual understanding and critical thinking skills still needs to be studied further. This study aims to analyze the implementation of Educaplay in primary school learning and its impact on students' conceptual understanding and critical thinking skills. This study used a qualitative approach with an exploratory descriptive design. Data were collected through interviews with teachers and students, classroom observations, and documentation studies. Data analysis was carried out using data reduction techniques, data presentation, and conclusion drawing based on the Miles and Huberman method. The results showed that the use of Educaplay was able to increase students' involvement and motivation in learning. Analysis of pretests and posttests revealed a significant increase in conceptual understanding in students who used Educaplay compared to conventional methods. In addition, the platform supports the implementation of instructional differentiation and assists teachers in monitoring student progress in real-time. However, the implementation of Educaplay faces challenges, such as limited infrastructure and teachers' lack of digital literacy. Therefore, training for educators and improving access to technology are needed to maximize the effectiveness of digital-based learning in primary schools.